Mid- to long-term follow-up of total shoulder arthroplasty using a keeled glenoid in young adults with primary glenohumeral arthritis - Denard, Patrick; Raiss, Patric; Sowa, Boris; Walch, Gilles (Journal of shoulder and elbow surgery, 2013)
Background - The purpose of this study was to examine the mid- to long-term functional outcome and implant survival of total shoulder arthroplasty (TSA) in adults aged 55 years or younger with primary glenohumeral arthritis. The hypothesis was that TSA would lead to improvement in functional outcome but that implant survival would decline between 5 years and 10 years postoperatively. - Materials and methods - Between 1992 and 2004, 52 TSAs were implanted in 8 centers for primary glenohumeral arthritis in patients aged 55 years or younger. Minimum follow-up of 5 years was available in 50 patients at a mean of 115.5 months postoperatively. Kaplan-Meier survivorship analysis was performed, and clinical outcome was assessed. - Results - After TSA, adjusted Constant scores improved from 37.0% to 73.4% and forward flexion improved from 97° to 128° (P < .001). The adjusted Constant score was 80.0 in patients free of revision of the glenoid compared with 43.6 in the group requiring revision of the glenoid (P < .001). Survivorship of the glenoid component with revision surgery for glenoid loosening as the endpoint was 98% (95% confidence interval, 89.4%-100%) at 5 years and 62.5% (95% confidence interval, 40.6%-81.2%) at 10 years. Factors associated with survival of the glenoid included anatomic humeral component positioning and a compaction glenoid preparation technique. - Conclusions - At 5 years' follow-up, TSA leads to improvement in functional outcome and a satisfactory implant survival rate of 98% in young adults with primary glenohumeral arthritis. However, the 10-year survival rate of TSA was only 62.5% in patients aged 55 years or younger at the time of surgery.
Gesehen am 11.12.2020